The endothelial protein C receptor impairs the antibacterial response in murine pneumococcal pneumonia and sepsis - Schouten, Marcel; Daan de Boer, J.; Kager, Liesbeth M.; Roelofs, Joris J. T. H.; Meijers, Joost C. M.; Esmon, Charles T.; Levi, Marcel; van ’t Veer, Cornelis; van der Poll, Tom (Thrombosis and Haemostasis, 2014)
Pneumococcal pneumonia is a frequent cause of gram-positive sepsis and has a high mortality. The endothelial protein C receptor (EPCR) has been implicated in both the activation of protein C (PC) and the anti-inflammatory actions of activated (A)PC. The aim of this study was to determine the role of the EPCR in murine pneumococcal pneumonia and sepsis. Wild-type (WT), EPCR knockout (KO) and Tie2-EPCR mice, which overexpress EPCR on the endothelium, were infected intranasally (pneumonia) or intravenously (sepsis) with viable Streptococcus pneumoniae and euthanised at 24 or 48 hours after initiation of the infection for analyses. Pneumonia did not alter constitutive EPCR expression on pulmonary endothelium but was associated with an influx of EPCR positive neutrophils into lung tissue. In pneumococcal pneumonia EPCR KO mice demonstrated diminished bacterial growth in the lungs and dissemination to spleen and liver, reduced neutrophil recruitment to the lungs and a mitigated inflammatory response. Moreover, EPCR KO mice displayed enhanced activation of coagulation in the early phase of disease. Correspondingly, in pneumococcal sepsis EPCR KO mice showed reduced bacterial growth in lung and liver and attenuated cytokine release. Conversely, EPCR-overexpressing mice displayed higher bacterial outgrowth in lung, blood, spleen and liver in pneumococcal sepsis. In conclusion, EPCR impairs antibacterial defense in both pneumococcal pneumonia and sepsis, which is associated with an enhanced pro-inflammatory response.
Keywords: Coagulation; endothelial protein C receptor; pneumonia; sepsis; Streptococcus pneumoniae